2015
DOI: 10.1016/j.jadohealth.2014.10.264
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health of Transgender Youth in Care at an Adolescent Urban Community Health Center: A Matched Retrospective Cohort Study

Abstract: Purpose Transgender youth represent a vulnerable population at risk for negative mental health outcomes including depression, anxiety, self-harm, and suicidality. Limited data exists to compare the mental health of transgender adolescents and emerging adults to cisgender youth accessing community-based clinical services; the current study aimed to fill this gap. Methods A retrospective cohort study of electronic health record (EHR) data from 180 transgender patients age 12–29 years seen between 2002–2011 at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
304
2
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 553 publications
(355 citation statements)
references
References 34 publications
18
304
2
7
Order By: Relevance
“…These findings, while striking, align with what has been reported in much of the previous literature on transgender patients. 2,[36][37][38][39] In addition, we observed disparities among older TMBs, who were entitled to Medicare based on age. Although rates of chronic conditions in this group were high for both TMBs and CMBs, many chronic conditions that typically occur or worsen in older ages were observed to be even more common among TMBs.…”
Section: Trans Medicare Beneficiaries and Chronic Conditions 407 Discusmentioning
confidence: 84%
“…These findings, while striking, align with what has been reported in much of the previous literature on transgender patients. 2,[36][37][38][39] In addition, we observed disparities among older TMBs, who were entitled to Medicare based on age. Although rates of chronic conditions in this group were high for both TMBs and CMBs, many chronic conditions that typically occur or worsen in older ages were observed to be even more common among TMBs.…”
Section: Trans Medicare Beneficiaries and Chronic Conditions 407 Discusmentioning
confidence: 84%
“…These studies showed that gender confirming medical treatment improves mental health, including anxiety symptomatology. However, the results are not consistent (e.g., Reisner et al, 2015) and limited by a small sample size (e.g., De Vries et al, 2014;Heylens et al, 2014b) or by the lack of matched controls (e.g., Colizzi et al, 2013Colizzi et al, , 2014Davis and Colton Meier, 2014;Gomez-Gil et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Research in the transgender population pre-treatment using cross sectional data, have shown high levels of anxiety symptomatology in this population (Bockting et al, 2013;de Vries et al, 2011;Heylens et al, 2014a;Reisner et al, 2015Reisner et al, , 2016. High levels of anxiety symptomatology are particularly prevalent in transgender people before treatment (Bergero-Miguel et al, 2016;Colizzi et al, 2013;de Vries et al, 2011;Gómez-Gil et al, 2012;Heylens et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research found significant differences between transgender and cisgender people in psychological variables such as anxiety, the level of depression, suicidal thoughts, and self-harm behaviour, which refers to emotional functioning (Reisner, 2015). According to Reisner,transgender participants (106 FtM,94 MtF) had higher scores than cisgender individuals on those measures.…”
mentioning
confidence: 99%